2019
DOI: 10.1021/acs.analchem.8b05885
|View full text |Cite
|
Sign up to set email alerts
|

Cavity Carbon-Nanopipette Electrodes for Dopamine Detection

Abstract: Microelectrodes are typically used for neurotransmitter detection, but nanoelectrodes are not because there is a trade-off between spatial resolution and sensitivity, which is dependent on surface area. Cavity carbon nanopipette electrodes (CNPEs), with tip diameters of a few hundred nanometers, have been developed for nano-scale electrochemistry. Here, we characterize the electrochemical performance of CNPEs with fast-scan cyclic voltammetry (FSCV) for the first time. Dopamine detection is compared at cavity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 56 publications
2
80
2
Order By: Relevance
“…In this case, an electrode is used as a “reading” instrument by immersing the film in a mediator solution (0.1 m m Fc, 0.1 m m Ru 3+ ), placing the electrode directly above the hydrogel, biasing the electrode to induce a mediator reaction (in our case, Fc oxidation was induced by imposing an oxidizing voltage +0.4 V versus Ag/AgCl), and linearly scanning the electrode across the surface (0.35 mm s −1 ) to detect the regions that can undergo redox‐cycling. [ 50–55 ] The first plot in Figure 2d shows that little Fc‐oxidation currents were measured in the unpatterned regions while considerably larger currents were observed in regions pattered with catechol. This larger current is consistent with the Fc mediator undergoing oxidative redox‐cycling in the patterned catechol region.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, an electrode is used as a “reading” instrument by immersing the film in a mediator solution (0.1 m m Fc, 0.1 m m Ru 3+ ), placing the electrode directly above the hydrogel, biasing the electrode to induce a mediator reaction (in our case, Fc oxidation was induced by imposing an oxidizing voltage +0.4 V versus Ag/AgCl), and linearly scanning the electrode across the surface (0.35 mm s −1 ) to detect the regions that can undergo redox‐cycling. [ 50–55 ] The first plot in Figure 2d shows that little Fc‐oxidation currents were measured in the unpatterned regions while considerably larger currents were observed in regions pattered with catechol. This larger current is consistent with the Fc mediator undergoing oxidative redox‐cycling in the patterned catechol region.…”
Section: Resultsmentioning
confidence: 99%
“…Yang et al reported a cavity carbon‐nanopipette electrodes (CNPE) with FSCV for dopamine detection with increased sensitivity compared to typical nanoelectrodes, and the detailed dopamine‐oxidation−reduction is shown in Figure 9A, and a modeled dopamine concentration change in the cavity is shown in Figure 9B 104 . The CNPEs have high selectivity for dopamine even in the presence of interfering AA.…”
Section: Electochemical Biosensors Based On Oxidation Of Dopaminementioning
confidence: 99%
“…CNPs prepared by chemical vapor deposition (CVD) of carbon into prepulled quartz nanopipettes have proven to be applicable to electroactive transmitter detection. 18 , 19 After modification with Pt black, they were also employed in measurements of reactive oxygen and nitrogen species inside single organelles and vesicles. 20 , 21 In this work, we controlled the orifice size of open CNPs in VIEC measurements, and the distribution of N molecules was correlated with the vesicle size.…”
mentioning
confidence: 99%